A study of values and strategy together in the organisation - Moller, Belinda (Trinity College (Dublin, Ireland). Trinity Business School, 2008)
This study answers a number of questions inadequately addressed by the literature. How has the history and development of the strategy concept reflected values and particularly, the contribution of the values of individuals? How has the field of strategy and values been ontologically, epistomologically and methodologically examined in relevent research? What methodology could be used to study values in the context of an organisation's strategy? What is the role of values in the founding and development of an organisation, and what role do values play in strategic incidents and in the response of individuals and groups who have a responsibility to the whole organisation? Finally, what are the consequences of values for the development of the organisation?
Keywords: Business Studies, Ph.D.; Ph.D. Trinity College Dublin